UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TPS PADA PESERTA DIDIK KELAS III SDN 35 KAMPUNG SAWAH - Ruswati Ruswati (STKIP Pesisir Selatan, 2018)
ABSTRACTTPS (Think-Pair-Share) or (Thinking-Pairing-Sharing) is a type of cooperative learning that is designed to influence the patterns of interaction of students. TPS requires students to help each other in small groups (2-6 members) and are more detailed by cooperative rewards, rather than individual rewards (Ibrahim et al: 2000: 3). Problems to be studied in this study are: Is it through the use of learning models cooperative type of polling station can improve Indonesian language learning outcomes of Class III students at SDN 35 Kampung Sawah? The purpose of this action research is to find out the improvement of Indonesian language learning outcomes through the use of TPS cooperative learning models in student IV.B SDN 35 Kampung Sawah. This uses two rounds of classroom action research. Each round consists of four stages, namely: planning, implementation, observation, reflection. The target of this study was Class III students of SDN 35 Kampung Sawah. The data obtained are quantitative and qualitative data. From the results of the analysis of each cycle, namely pre cycle (48.72%), cycle I (76.92%), cycle II (97.44%) .The conclusion of this study is the TPS cooperative learning model has a positive influence , which can improve student learning outcomes as indicated by the average answers of students stating that students are interested and interested in the TPS cooperative learning model so that they become motivated to learn.